Experimental and finite element analysis of dynamic loading of the mouse forearm. Issue 12 (5th September 2014) - Thiagarajan, Ganesh; Lu, Yunkai; Dallas, Mark; Johnson, Mark L.
ABSTRACT Bone formation is reported to initiate in osteocytes by mechanotransduction due to dynamic loading of bone. The first step towards this is to characterize the dynamic strain fields in the overall bone. Here, the previously developed mouse forearm ulna‐radius model, subjected to static loading, has been further enhanced by incorporating a loading cap and applying a cyclic dynamic load to more closely approximate experimental biological conditions. This study also incorporates data obtained from strain gauging both the ulna and radius simultaneously. Based on separate experiments, the elastic modulus of the ulna and radius were determined to be 13.8 and 9.9 GPa, respectively. Another novel aspect of the numerical model is the inclusion of the interosseous membrane in the FE model with membrane stiffness ranging from 5–15 N/mm that have been found to give strain values closer to that from the experiments. Interestingly, the inclusion of the interosseous membrane helped to equalize the peak strain magnitudes in the ulna and radius (∼1800 at 2 N load and ∼3200 at 3.5 N), which was also observed experimentally. This model represents a significant advance towards being able to simulate through FE analysis the strain fields generated in vivo upon mechanical loading of the mouse forearm. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1580–1588, 2014.